How to Do Things with Things: Craft at the Edge of Buber’s Philosophical Anthropology - Atlas, Dustin (Images, 2019)
Abstract This article offers an alternative reading of Martin Buber (1878–1956), one guided by his writings on craft and artistic creation. Rather than view Buber as a philosopher of dialogue, it views him as a philosopher of relationships, including relationships to nonhuman things. His writings on craft and artistic creation are taken to exemplify these nonhuman relationships. After sketching out the general structure of Buber’s thought, and the role that nonhuman relationships play in it, this article traces a trajectory through Buber’s work, showing the ever-increasing importance of these relationships through an analysis of his treatments of art and craft. It ends with an analysis of his late anthropological work on craft and images, which demonstrates that this was a longstanding, if not central, concern of Buber’s that guided not only his treatment of material things, but his understanding of Judaism as well.